Correlation Between Lead Levels and Percentage of Basophilic Stippling in the Blood of Silver Men - Ratu Azzahra; Kurnia Ritma Dhanti; Asmiyenti Djaliasrin Djalil; Retno Sulistiyowati (Indonesian Journal of Global Health Research, 2025)
The phenomenon of silver men has become increasingly prevalent in recent years. The direct application of metallic paint to the body and the nature of their activities are major factors contributing to potential lead expsure. Elevated blood lead levels can disrupt hematopoiesis, leading to various blood abnormalities, including the presence of basophilic stippling. Basophilic stippling is a distinctive marker indicative of heavy metal toxicity, particularly lead poisoning. This study aims to examine the correlation between blood lead levels and the presence of basophilic stippling in the blood of silver men in Purbalingga Regency and Purwokerto Sub-district. This study employed an observational analytical design with a cross-sectional approach. The research sample consisted of blood specimens from 14 silver men, selected using accidental sampling. Blood samples (3 mL) were collected from the respondents arms into EDTA tubes. Blood lead levels were analyzed using Atomic Absorption Spectrophotometry (AAS), while basophilic stippling was examined through Giemsa-stained blood smears observed under a microscope. The collected data were analyzed using Pearsons correlation test. The Pearson correlation test yielded a p-value of 0.045 (p 0.05) and a correlation coefficient of 0.542, indicating a strong positive correlation. There is a strong correlation between blood lead levels andthe presence of basophilic stippling in silver men. An increase in blood lead levels is accompanied by the occurrence of basophilic stippling, highlighting the potential toxic effects of lead exposure in this population.